PENGARUH INOVASI PRODUK, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KINERJA PEMASARAN PRODUK PT WINGS FOOD - Nugraheni, Intan Natalia; Wulandari, Dewi Sri; Puspitorini, Ferawaty (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze this influence of product innovation, product quality and brand image on marketing performance at PT Wings Food product. The increasing intensity of business competition drives companies to implement affective marketing strategies in order to maintain and improve their performance. This reseach uses a quantitative approach with descriptive and verification methods. The population of this study consists of consumers of PT Wings Food product residing in Villa Mutiara Gading 2 Housing, Bekasi, North Tambun. With a sample size of 136 respondents, determined using the Slovin formula. Data was collected through questionnaires and analyzed using multiple linier regression analysis. The result show that both partially and simultaneously, product innovation, product quality and brand imagae significanty influence marketing performance. Therefore, the company should contionue to innovation, maintain product quality and strengthen its brand image in order to remain competitive and echance marketing performance.